The Nexus Between FDR, NPF, BOPO Toward Profitability Of Indonesian Islamic Bank - Ayu Gusmawanti; Supaijo Supaijo; Muhammad Iqbal; Muhammad Iqbal Fasa (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractBased on Sharia Commercial Bank Statistics Data, the value of profitability is measured by Return On Assets that have decreased from 2013-2017. This happens because the NPF ratio has increased from year to year (if there is much problematic financing, the cost of providing a loss will be high, which causes the BOPO ratio to increase). So that Sharia Commercial Banks must reduce the FDR ratio, with the reduction in the distribution of funds to customers making the Sharia Commercial Banks experience a reduction in income to be received. That way can cause the level of profitability to be obtained decreases. This study aims to determine the effect of the ratio of FDR, NPF, BOPO to the profitability of Islamic Commercial Banks in Indonesia. This type of research is descriptive quantitative with panel data regression analysis methods and hypothesis testing using (F test, t-test, R2), and data processing using Eviews 9. The test results obtained together with variables FDR, NPF, BOPO significantly influence towards ROA. Partially, FDR has no significant negative effect on ROA. NPF variable is not a significant positive effect on ROA. BOPO variable has a negative and significant effect on ROA. R2 test of 82.73% while the remaining 17.27% is influenced by other factors outside the study. BOPO variable has a negative and significant effect on ROA. R2 test of 82.73% while the remaining 17.27% is influenced by other factors outside the study. BOPO variable has a negative and significant effect on ROA. R2 test of 82.73% while the remaining 17.27% is influenced by other factors outside the study.Keywords: FDR, NPF, BOPO and ROAAbstrakBerdasarkan Data Statistik Bank Umum Syariah nilai profitabilitas yang di ukur dengan Return On Asset mengalami penurunan dari tahun 2013-2017. Hal tersebut terjadi karena rasio NPF mengalami peningkatan dari tahun ke tahun (apabila banyak nya pembiayaan bermasalah maka biaya pencadangan atas kerugian akan tinggi yang mengakibatkan rasio BOPO meningkat). Sehingga Bank Umum Syariah harus mengurangi rasio FDR, dengan berkurangnya penyaluran dana kepada nasabah membuat Bank Umum Syariah mengalami pengurangan atas pendapatan yang akan diterima. Dengan begitu dapat menyebabkan tingkat profitabilitas yang akan di dapat menurun. Penelitian ini bertujuan untuk mengetahui pengaruh rasio FDR, NPF, BOPO terhadap profitabilitas Bank Umum Syariah di Indonesia. Jenis penelitian ini adalah deskriptif kuantitatif dengan metode analisis regresi data panel dan uji hipotesis menggunakan (uji F, uji t, R2), serta pengolahan data nya menggunakan aplikasi Eviews9. Hasil pengujian di peroleh secara bersama-sama variabel FDR, NPF, BOPO berpengaruh secara signifikan terhadap ROA. Secara parsial, FDR berpengaruh negative tidak signifikan terhadap ROA. Variabel NPF berpengaruh positif tidak signifikan terhadap ROA.Variabel BOPO berpengaruh negative dan signifikan terhadap ROA. Uji R2 sebesar 82,73% sedangkan sisanya sebesar 17,27% dipengaruhi oleh faktor-faktor lain di luar penelitian.Kata Kunci: FDR, NPF, BOPO, dan ROA